Effect of Leg Strength Exercises on Fatigue Level in Patients Undergoing Hemodialysis: A Clinical Trial - Jabbar , Ilham Ghanam; Mahmood , Fatma Makee (Kerbala Journal of Nursing and Health Sciences., 2025)
Introduction: Hemodialysis serves as a main treatment method for these patients. It results in several complications like fatigue and decreased activities of daily living. Legs strength exercises are an effective method to minimize fatigue and for improving activities of daily living. Methods: A purposive (non-probability) sample consists of 137 patients selected from patients with CKD who are undergoing HD and were treated at Imam Al-Hussein in Habib Ibn Mudaher center and hemodialysis wards of Imam Al-Hassan Al-Mujtaba Teaching Hospital in Holy Kerbala. The data were collected through interview using two scales that are socio-demographic and clinical data Questionnaire and Functional Assessment of Chronic Illness Therapy (FACIT) Fatigue Scale (Version 4) and the data were analyzed and interpreted using of the application of Statistical Package for Social Sciences (SPSS) version 26.0. Results: The study group showed a significant reduction in fatigue, with mean scores dropping from 39.60 (SD = 6.702) pre-test to 3.33 (SD = 2.832) post-test, Conversely, the control group's showed no improvement, with the mean fatigue score increasing slightly from 40.95 (SD = 4.386) in the pre-test to 41.84 (SD = 3.031) in the post-test. Conclusion: Legs strength exercises were beneficial in decreasing fatigue level in patients undergoing haemodialysis.